A New Model of Coupled Hindmarsh-Rose Neurons (Journal of Nonlinear Modeling and Analysis, 2024)
A new model of two coupled neurons is presented by the partly diffusive Hindmarsh-Rose equations. The solution semiflow exhibits globally absorbing characteristics. As the main result, the self-synchronization of the coupled neurons at a uniform rate is proved, which can be extended to complex neuronal networks.